How do voters react to welfare reforms? - Jensen, Carsten; Lee, Seonghui; Arndt, Christoph; Wenzelburger, Georg (Politica, 2016)
Welfare state scholars debate whether reforms of the welfare state affect governments’ popularity. We have collected yearly data on reforms of old age pensions and unemployment protection in the United Kingdom back to 1946, which allows us to statistically test if welfare reforms affect government support. It does. Cutbacks reduce support, and expansions increase it. Especially the last result is interesting because the literature mostly focuses on cutbacks. Our results suggest that there is an almost symmetrical relationship, meaning that cutbacks and expansions have roughly the same effect, but in opposite directions.